The Qur’anic Movement Gerakan Ayo Mengaji (Gerami) in Jambi: An Intersectional Analysis of Women, Gender, and Class - Maghfirah, Moona; Rafiq, Ahmad (Al-Jami'ah: Journal of Islamic Studies, 2025)
This article demonstrates that women’s experiences within religious movements are diverse and multifaceted, shaped by a complex interplay of social factors. By investigating ‘Gerakan Ayo Mengaji’ (GERAMI) as Quranic movement in Jambi City, it applies an intersectional lens to examine how gender and class dynamics influence Muslim women’s experiences within the movement, such as their space, roles, and performance. Drawing on in-depth interviews, participant observation, and the movement’s archival materials, the study analyzes the identities and activism of GERAMI’s women members. The findings suggest that the intersectionality of gender identities enables the movement to function not only as a source of Muslim women’s identity formation but also as a means of reinforcing or contesting gendered social structures. The intersection of various forms of individual capital significantly shapes members’ roles and performances within the movement, thereby constructing internal hierarchies. The article argues that the convergence of diverse social identities within a Qur’anic movement can inadvertently produce hierarchical power dynamics, leading to the emergence of new gendered public spaces and class structures within the movement itself.[Artikel ini menunjukkan bahwa pengalaman perempuan dalam gerakan keagamaan bersifat beragam dan memiliki banyak sisi, yang dibentuk oleh interaksi kompleks faktor-faktor sosial. Dengan mengkaji ‘Gerakan Ayo Mengaji’ (GERAMI) sebagai gerakan Al-Quran di Kota Jambi, penelitian ini menggunakan lensa interseksional untuk menganalisis bagaimana dinamika gender dan kelas memengaruhi pengalaman perempuan Muslim dalam gerakan tersebut, termasuk ruang, peran, dan aktivitas mereka. Menggunakan wawancara mendalam, pengamatan partisipatif, dan bahan arsip gerakan, studi ini menganalisis identitas dan aktivisme anggota perempuan GERAMI. Temuan menunjukkan bahwa interseksionalitas identitas gender memungkinkan gerakan ini berfungsi tidak hanya sebagai sumber pembentukan identitas perempuan Muslim, tetapi juga sebagai sarana untuk memperkuat atau menantang struktur sosial yang berorientasi gender. Selain itu, persilangan berbagai bentuk modal individu secara signifikan membentuk peran dan kinerja anggota dalam gerakan, sehingga membentuk hierarki internal. Pada akhirnya, artikel ini berargumen bahwa konvergensi identitas sosial yang beragam dalam gerakan Qur’anik dapat secara tidak sengaja menghasilkan dinamika kekuasaan hierarkis, yang mengakibatkan munculnya ruang publik berjenis kelamin baru dan struktur kelas di dalam gerakan itu sendiri.]